DEVELOPING LISTENING AND SPEAKING SKILLS IN ESL LEARNERS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In the realm of English as a Second Language (ESL) education, fostering effective listening and speaking skills is paramount. This article delves into strategies and approaches for developing these crucial language competencies among ESL learners. From the importance of a communicative approach to specific classroom techniques, we explore a comprehensive guide to enhancing listening and speaking abilities.